Reviewing the needs of forward deployed critical care: South Sudan and the future. Issue 5 (7th September 2021) - Bulleid, Victoria; Hooper, T; Nordmann, G
Abstract : The UK military medical treatment facility (MTF) that deployed to the United Nations Mission in South Sudan in 2017 was based on a facility that can provide damage control surgery and resuscitation for soldiers with ballistic trauma injuries. It had to be supplemented with additional medical equipment and drugs that could support a peacekeeping mission in Africa. The clinicians used this experience and opportunity to review the critical care capability of UK Army Medical Services forward MTFs and recommend changes to reflect the increasing contemporaneous need on recent deployments to support more casualties with medical, infectious diseases and other non-battle injuries and illnesses. A concurrent review of the facility's critical care transfer equipment was also undertaken and allowed it to be adapted for use as either transfer equipment or as a critical care surge capability, to increase the facility's critical care capacity.